2000
DOI: 10.1002/(sici)1097-4636(20000305)49:3<415::aid-jbm15>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption and release of insulin-like growth factor-I on porous tricalcium phosphate implant

Abstract: In order to develop bone substitutes, the design of biomaterials like calcium phosphate ceramic loaded with bone growth factor are of great interest. However, it is necessary to control the amount of growth factor adsorbed onto ceramics and the kinetics of its release. Radiolabeling of insulin-like growth factor-I (IGF-I) with 125-iodine ([(125)I]-IGF-I) and its adsorption onto porous tricalcium phosphate (TCP) cylinders enabled us to establish the time-adsorption and time-release curves using various concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(25 citation statements)
references
References 32 publications
2
23
0
Order By: Relevance
“…However, a successful bone substitute must have two crucial characteristics: osteoconductive biodegradable matrices that promote cellular attachment and proliferation, and a set of stimulators that promote cell growth and differentiation. [26][27][28] The authors of this study previously developed a bone substitute, the GGT composite, which mimicked natural bone and was composed of an organic phase, gelatin and a mineral phase-an apatite-like tricalcium phosphate.…”
Section: Discussionmentioning
confidence: 99%
“…However, a successful bone substitute must have two crucial characteristics: osteoconductive biodegradable matrices that promote cellular attachment and proliferation, and a set of stimulators that promote cell growth and differentiation. [26][27][28] The authors of this study previously developed a bone substitute, the GGT composite, which mimicked natural bone and was composed of an organic phase, gelatin and a mineral phase-an apatite-like tricalcium phosphate.…”
Section: Discussionmentioning
confidence: 99%
“…The release of these factors occurs either spontaneously or as a consequence of the bony replacement of the implant. There have been numerous reports on osseous integration of organic and inorganic implant materials releasing growth factors like bone morphogenetic protein 2 (BMP-2) [4-7], bone morphogenetic protein 7 (BMP-7) [8], fibroblast growth factor 2 (FGF-2) [9], platelet-derived growth factor [10], and insulin-like growth factors [11]. Some of these products are available for routine procedures.…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 20% of the IGF-I loaded in PLGA microspheres, using the same type of PLGA (50:50) polymer as in the present study, was released within the first 24 hours of a 13-18 day degradation time, releasing 1.1 to 2.2 μg of IGF-1 [30, 31]. IGF-I burst release also occurs in other scaffold types, such as tricalcium phosphate, which released 10-78% of the protein within 24 hours when degraded in water and serum, respectively [32]. The present results, however, showed that sintering the microspheres into a scaffold reduced the 24 hour burst, with 20% release not reached until three days.…”
Section: Discussionmentioning
confidence: 93%